A complex-variable finite element method-based inverse methodology to extract constitutive parameters using experimental data. (15th May 2022) - Ramirez-Tamayo, Daniel; Soulami, Ayoub; Gupta, Varun; Restrepo, David; Montoya, Arturo; Nickerson, Ethan; Roosendaal, Timothy; Simmons, Kevin; Petrossian, Gayaneh; Millwater, Harry
Abstract: This paper presents the use of full-field kinematic measurements obtained using the digital image correlation (DIC) procedure and load–displacement data to determine constitutive material properties by solving an inverse finite element optimization problem. A key ingredient in the proposed approach is computing accurate sensitivities with respect to the unknown parameters. These sensitivities were used to solve the optimization problem using an accurate, efficient, gradient-based method, and were computed using the complex-variable finite element method, ZFEM. The use of ZFEM's gradients to inversely determine material properties is demonstrated with two examples. First, the elastic–plastic material properties of DP-590 steel are obtained using a tensile test specimen. Second, the cohesive material parameters of an adhesive are determined using a double cantilever beam test. A significant outcome of this paper is that the use of a weighted residual formulation of the interfacial strain fields and the load–displacement data within the optimization procedure provides better estimates of the constitutive properties than using only the load–displacement data. This technique minimizes the relative error in both the strain fields and the load–displacement curve, which is important to obtain accurate interfacial properties.